Accès aux services sociaux et de santé en français : l’expérience des Franco-Manitobains - de Moissac, Danielle; Giasson, Florette; Roch-Gagné, Margaux (Minorités linguistiques et société, 2015)
Des progrès considérables sont constatés dans l’offre de services et la formation de professionnels dans le domaine des services sociaux et de santé en français au Manitoba depuis les 30 dernières années. L’objectif de cette recherche est de mieux connaître la perception des usagers quant aux services couramment disponibles et aux barrières réduisant l’accès à ces services. L’obtention de services en français est importante pour la population francophone, particulièrement pour les aînés et les immigrants. En moyenne, 50 % des répondants disent demander des services en français, mais seulement 25 % affirment les recevoir. La pénurie de professionnels pouvant offrir des services en français est considérée comme la barrière principale à l’accès. L’offre active est essentielle et facilite la prestation des services dans la langue de choix de la clientèle. Mots-clés : accessibilité, santé, services sociaux, Manitoba, minorité francophone

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Barriers in accessing HIV care for Francophone African, Caribbean and Black people living with HIV in Canada: A scoping review - Djiadeu, Pascal; Yusuf, Abban; Ongolo-Zogo, Clémence; Nguemo, Joseph; Odhiambo, Apondi J.; Mukandoli, Chantal; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2020)
Introduction In 2001, 50%–55% of French-speaking minority communities did not have access to health services in French in Canada. Although Canada is officially a bilingual country, reports indicate that many healthcare services offered in French in Anglophone provinces are insufficient or substandard, leading to healthcare discrepancies among Canada’s minority Francophone communities. Objectives The primary aim of this scoping systematic review was to identify existing gaps in HIV-care delivery to Francophone minorities living with HIV in Canada. Study design Scoping systematic review. Data sources Search for studies published between 1990 and November 2019 reporting on health and healthcare in Francophone populations in Canada. Nine databases were searched, including Medline, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, the National Health Service Economic Development Database, Global Health, PsychInfo, PubMed, Scopus and Web of Science. Study selection English or French language studies that include data on French-speaking people with HIV in an Anglophone majority Canadian province. Results The literature search resulted in 294 studies. A total of 230 studies were excluded after duplicates were removed. The full texts of 43 potentially relevant papers were retrieved for evaluation and data extraction. Forty-one studies were further excluded based on failure to meet the inclusion criteria leaving two qualitative studies that met our inclusion criteria. These two studies reported on barriers on access to specialised care by Francophone and highlighted difficulties experienced by healthcare professionals in providing quality healthcare to Francophone patients in Ontario and Manitoba. Conclusion The findings of this scoping systematic review highlight the need for more HIV research on linguistic minority communities and should inform health policymaking and HIV/AIDS community organisations in providing HIV care to Francophone immigrants and Canadians.

Vers des services attirants, accessibles et pertinents pour les personnes âgées immigrantes francophones ? - Nduwimana, Mathilde; Home, A. (Reflets, 1995)
Cet article décrit et analyse les besoins et préoccupations des personnes âgées autonomes appartenant aux groupes ethniques francophones et résidant dans Ottawa-Carleton. L'objectif principal est d'explorer les raisons pour lesquelles elles utilisent peu les services de soutien communautaires pour les personnes âgées francophones. Nous avons effectué des entrevues semi-structurées auprès de quatre représentantes et de six personnes âgées des communautés ethno-culturelles francophones, et nous avons effectué une analyse de contenu par thème. Les répondantes ont souligné les besoins de contacts sociaux, d'apprentissage du français et/ou de l'anglais, d'accès aux moyens financiers adéquats et d'information sur les ressources disponibles. Des obstacles liés au contexte socio-écono-politique dans la société d'accueil entravent la satisfaction de ces besoins. La levée de certaines barrières concrètes, la modification des politiques sociales et des pratiques d'intervention faciliteraient l'accès aux services par les personnes âgées des groupes ethniques francophones et augmenteraient leurs options.

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)
https://pmc.ncbi.nlm.nih.gov/articles/PMC2231483/

Immigration et santé. Où en sont les Francophones ? Une enquête sur l'état de santé des immigrants francophones en Colombie-Britannique - Poullos, Nichollos (RésoSanté Colombie-Britannique, 2018)

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.